COMPARISION OF THE EFFICACY OF CARVEDILPL AND PROPRANOLOL IN THE SECONDARY PREVENTION OF ESOPHAGEAL VARICEAL BLEEDING - Irshad Ahmed; Aamir Husain; Muhammad Waqas (Journal of University Medical & Dental College, 2016)
ABSTRACT: Objective: The study was done to compare the efficacy of carvedilol and propranolol in the secondary prevention of upper gastrointestinal bleeding due to esophageal varices. Study Design: Randomized Controlled Trial Setting: Medical Unit II, Allied Hospital Faisalabad. Duration of Study: 30th Jan, 2015 to 30th June, 2015. Sample Size: Sample size was 94 as calculated by WHO sample size calculator Sampling Technique: Non-probability consecutive sampling Patients and Methods: 94 patients presenting with upper GI bleed and having esophageal varices on endoscopy were included in the study. They were divided into two groups. Group A was given propranolol. Group B was given carvedilol. Doppler ultrasonography was done at the start of the study and at the end of the study. Paired Sample T Test was applied to the portal vein diameter. Results Mean portal vein diameter was 12.85±0.807cm at the start of the study and 11.04±0.808 cm at 24th week of study in Group A (P value = 0.00). Mean portal vein diameter was 12.77±0.633 cm at the start of the study and 11.49±0.953 cm at 24th week of study in Group B (P value = 0.00). Bleeding was effectively reduced in 35 patients (74.46%) in Group A and 35 patients (74.46%) in Group B (P value = 0.593).